Aromatase Inhibitors: New Drug of Choice for Induction of Ovulation - Siddiqui, M; Mahmud, N; Begum, MR; Chowdhury, TA (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Anovulation accounts for around 20% cases of infertility even when other fertility factors are normal. Clomiphene Citrate (CC), the oral anti-estrogen has long been used as the first line drug for induction of ovulation. Clomiphene is associated with a high ovulation (60-80%) but relatively poor pregnancy rate (30-40%). CC leads to long lasting estrogen receptor depletion. Because of its long half-life (2 weeks), CC possibly exerts a negative feedback effect on the cervical mucous and endometrial development with subsequent implantation failure. The aromatase inhibitor letrozole (originally approved for use in postmenopausal women with breast cancer to suppress estrogen production) is now increasingly being used by fertility specialists worldwide for ovulation induction.With a halflife of around 45 hours, letrozole possibly avoids the adverse effects of CC on endometrium. Preliminary trials have shown impressive prospects of aromatase inhibitor letrozole for induction of ovulation (even in CC resistant cases) with satisfactory pregnancy rates. Letrozole is now being marketed by our local pharmaceutical companies. Though large scale randomized controlled trials are not yet available, letrozole holds a very promising chance of replacing CC in near future. DOI: 10.3329/jbcps.v28i1.4642 J Bangladesh Coll Phys Surg 2010; 28: 40-44